Radiotherapy plus cetuximab or cisplatin in human papillomavirus-positive oropharyngeal cancer (NRG Oncology RTOG 1016): a randomised, multicentre, non-inferiority trial. Issue 10166 (5th January 2019) - Gillison, Maura L; Trotti, Andy M; Harris, Jonathan; Eisbruch, Avraham; Harari, Paul M; Adelstein, David J; Jordan, Richard C K; Zhao, Weiqiang; Sturgis, Erich M; Burtness, Barbara; Ridge, John A; Ringash, Jolie; et al.
Summary: Background: Patients with human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma have high survival when treated with radiotherapy plus cisplatin. Whether replacement of cisplatin with cetuximab—an antibody against the epidermal growth factor receptor—can preserve high survival and reduce treatment toxicity is unknown. We investigated whether cetuximab would maintain a high proportion of patient survival and reduce acute and late toxicity. Methods: RTOG 1016 was a randomised, multicentre, non-inferiority trial at 182 health-care centres in the USA and Canada. Eligibility criteria included histologically confirmed HPV-positive oropharyngeal carcinoma; American Joint Committee on Cancer 7th edition clinical categories T1–T2, N2a–N3 M0 or T3–T4, N0–N3 M0; Zubrod performance status 0 or 1; age at least 18 years; and adequate bone marrow, hepatic, and renal function. We randomly assigned patients (1:1) to receive either radiotherapy plus cetuximab or radiotherapy plus cisplatin. Randomisation was balanced by using randomly permuted blocks, and patients were stratified by T category (T1–T2 vs T3–T4), N category (N0–N2a vs N2b–N3), Zubrod performance status (0 vs 1), and tobacco smoking history (≤10 pack-years vs >10 pack-years). Patients were assigned to receive either intravenous cetuximab at a loading dose of 400 mg/m 2 5–7 days before radiotherapy initiation, followed by cetuximab 250 mg/m 2 weekly for seven doses (total 2150 mg/m 2 ), or cisplatin 100 mg/m 2 on days 1 and 22 of radiotherapy (total 200 mg/m 2 ). All patients received accelerated intensity-modulated radiotherapy delivered at 70 Gy in 35 fractions over 6 weeks at six fractions per week (with two fractions given on one day, at least 6 h apart). The primary endpoint was overall survival, defined as time from randomisation to death from any cause, with non-inferiority margin 1·45. Primary analysis was based on the modified intention-to-treat approach, whereby all patients meeting eligibility criteria are included. This study is registered with ClinicalTrials.gov, number NCT01302834 . Findings: Between June 9, 2011, and July 31, 2014, 987 patients were enrolled, of whom 849 were randomly assigned to receive radiotherapy plus cetuximab (n=425) or radiotherapy plus cisplatin (n=424). 399 patients assigned to receive cetuximab and 406 patients assigned to receive cisplatin were subsequently eligible. After median follow-up duration of 4·5 years, radiotherapy plus cetuximab did not meet the non-inferiority criteria for overall survival (hazard ratio [HR] 1·45, one-sided 95% upper CI 1·94; p=0·5056 for non-inferiority; one-sided log-rank p=0·0163). Estimated 5-year overall survival was 77·9% (95% CI 73·4–82·5) in the cetuximab group versus 84·6% (80·6–88·6) in the cisplatin group. Progression-free survival was significantly lower in the cetuximab group compared with the cisplatin group (HR 1·72, 95% CI 1·29–2·29; p=0·0002; 5-year progression-free survival 67·3%, 95% CI 62·4–72·2 vs 78·4%, 73·8–83·0), and locoregional failure was significantly higher in the cetuximab group compared with the cisplatin group (HR 2·05, 95% CI 1·35–3·10; 5-year proportions 17·3%, 95% CI 13·7–21·4 vs 9·9%, 6·9–13·6). Proportions of acute moderate to severe toxicity (77·4%, 95% CI 73·0–81·5 vs 81·7%, 77·5–85·3; p=0·1586) and late moderate to severe toxicity (16·5%, 95% CI 12·9–20·7 vs 20·4%, 16·4–24·8; p=0·1904) were similar between the cetuximab and cisplatin groups. Interpretation: For patients with HPV-positive oropharyngeal carcinoma, radiotherapy plus cetuximab showed inferior overall survival and progression-free survival compared with radiotherapy plus cisplatin. Radiotherapy plus cisplatin is the standard of care for eligible patients with HPV-positive oropharyngeal carcinoma. Funding: National Cancer Institute USA, Eli Lilly, and The Oral Cancer Foundation.